(untitled) (Journal of National Institute of Ophthalmology, 2026)
Purpose: To compare the efficacy of intravitreal bevacizumab (IVB) and the combination of IVB and intravitreal triamcinolone (IVT) in the treatment of centre involving DME patients. Methodology: This prospective observational study was conducted on 60 eyes of 60 patients of diabetic macular oedema attending in department of Vitreo-retina, they were selected purposively based on specific criteria. All patients underwent general preoperative routine examinations, electrocardiogram and blood tests that included glycosylated hemoglobin (HbA1c). All selected patient underwent detailed ocular and systemic examination as well as relevant investigations with special attention to assessment visual acuity and measurement of central macular thickness by OCT. Selected patients were grouped into group-A and group-B. They were randomly assigned with intra-vitreal injection of bevacizumab (1.25mg/0.05ml) in group-A and combination of intra-vitreal bevacizumab (1.25mg/0.05ml)and triamcinolone (1mg/0.05ml) in group-B. Injections were given monthly for 3 months in every patients. They were followed-up after 1 month and 3 months of injection. Best-corrected visual acuity (BCVA) in log MAR unit, central macular thickness (CMT) in μm by OCT, IOP by Goldman applanation tomnometry were done in every follow-up. Mean value of BCVA, CMT, cataract grading and IOP during follow-up periods were compared with that of baseline value to assess the significance of changes within the group as well as with other group to assess the significance of changes between the groups. Statistical analysis were done by using window software SPSS ver. 21. Chi-square test, paired and un-paired ’t’ test were done in applicable cases. p<0.05 were considered as significant. Results: In this study, the mean age of the study subjects of group A was 52.67±9.367 (SD) years and group B was 50.77±11.896 (SD) years. In this study Baseline mean BCVA was 0.99±0.59 for group- A and 0.94±0.52 for group- B. After one month it became .80±.48 for group A and 0.85±0.46 for group B. Again, it was 0.74±0.44 for group A and 0.80±0.43 for group B after three months. In both group A and group B after 1 month and 3 months follow up BCVA improve from baseline, but the changes between the two groups is statistically non- significant. In this study Baseline mean CMT was 441.03±37.74 μm for group-A and 440.26±160.71 μm for group- B patients which is non-significant. In group-A patients mean CMT became 362.00±100.00 (SD) μm microns and 299.77±73.98 (SD) μm in 1st and 2nd follow-up periods successively. In group B patients it became 354.57±102.301 (SD) μm and 286.10±69.61 (SD) μm in 1st and 2nd follow-up period respectively. There is significant reduction of mean CMT in different follow-up periods within the groups. There is more reduction of CMT in group B than group A both in after 1 month and after 3 month follow up but this is not statistically significant. Conclusion: Quantitative assessment and analysis of the data of this showed that though the visual acuity and central macular thickness improved from baseline after intra-vitreal injection of injection bivacizumab and combination of bevacizumab with triamicolone acitonide in follow-up periods but it was not significantly different between two groups. J.Natl.Inst.Ophthalmol.2024;7(1): 41-48